COVID-19 and Tuberculosis Coinfection: An Overview of Case Reports/Case Series and Meta-Analysis - Song, Wan-mei; Zhao, Jing-yu; Zhang, Qian-yun; Liu, Si-qi; Zhu, Xue-han; An, Qi-qi; Xu, Ting-ting; Li, Shi-jin; Liu, Jin-yue; Tao, Ning-ning; Liu, Yao; Li, Yi-fan; et al. (Frontiers in Medicine, 2021)
Background: Coronavirus disease– 2019 (COVID-19) and tuberculosis (TB) are two major infectious diseases causing hugeposing significant public health challengesthreats, and their co-infection (aptly abbreviated as COVID-TB) even makes theis situation worse. This study aimed to investigate the clinical features and prognosis of COVID-TB cases. Methods: Databases ofThe PubMed, Embase, Cochrane, CNKI, and Wanfang databases were searched for relevant studies until published through December 18, 2020. We made aAn overview of COVID-TB case reports/case series was prepared, and described their clinical characteristics and differences between survivors and deceased patientseath. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) forof death or severe COVID-TB19 cases from COVID-TB group were calculated. The quality of outcomes was assessed through theusing GRADEpro. Results: Thirty-six studies were included. Of 89 COVID-TB patients, 19 (23.46%) cases died, and 72 (80.90%) were male. The Median median age of the non-survivors (53.95±19.78 years) was older greater than the that of survivors (37.76±15.54 years), ) (P<0.001). The nNon-survivors were more likely to have hypertension (47.06% vs 17.95%), or have symptoms of dyspnea (72.73% vs 30%), or have bilateral lesions (73.68% vs 47.14%), infiltrates (57.89% vs 24.29%), tree in bud (10.53% vs 0%),, or have a higher level of leucocyte count (12.9 [10.5–-16.73] vs 8.015 [4.8–-8.97] × ×109/L) than survivors, (P<0.05). In terms of treatingtreatment, 88.52% received anti-TB therapy, 50.82% received antibiotics, 22.95% received antiviral treatmenttherapy, 26.23% received hydroxychloroquine, and 11.48% received corticosteroids. The pooled ORs of death or severe disease in the COVID-TB group compared withand non-TB group was were 2.21 (95% CI : 1.80, 2.70) and 2.77 (95% CI : 1.33, 5.74), (P<0.01). Conclusion: In summary, there may haveappear to be some predictors of worse prognosis among COVID-TB cases. There wasA moderate level of evidence suggests that COVID-TB cases patients arewere more likely to become suffer severe disease or death or severe cases than COVID-19 patients. Finally, a routine screening for TB may be recommended among suspected or confirmed cases of COVID-19 in countries with high TB high burden countries.